Memorial reparation: Women’s work of remembrance, repair and restoration in rural Colombia (2023)
ABSTRACT: The article discusses the reparative textile-making practices of three women’s sewing collectives in Colombia. Textile making and crafting is also a memory work which intersects and negotiates with different geographies, temporalities and scales of human subjectivity, social interaction and ecological belonging. We approach textile memory work as a practice embedded in a complex net of other everyday practices, spaces, and human and non-human beings, enabling the production of collective memories, while facilitating transformational processes by which women materially resignify and recover their communities affected by war. Textile memory work is a socially and ecologically situated practice of repair and reparation from below.